Electrospinning of polycaprolactone nanofibrous mat filled with heavy metal-adsorbing nanoparticles - Araño, Khryslyn G. (2012)
Nanomaterials have been proven to have superior properties compared to materials with dimensions above the nanoscale range. in this study, nanofibrous mat were produced from suspensions of iron-modified montmorillonite, i.e. FeMMT and ZVIMMT, in polycaprolactone by electrospinning process to understand the effects of polymer solution and suspension properties on the produced electrospun nanofibers. Suspensions were prepared by dissolving polycaprolactone in dichloromethane solvent and mixing varying amounts of montmorillonite to the solution. Characterizations of the suspension revealed that a 40% increase in polymer concentration in the solution resulted to an increase in viscosity from 94.9 cP to 302.7 cP. Additionally, increase in montmorillonite loading from 10 to 20% in a low viscosity polymer solution resulted to an increase in viscosity from 174.9 cP to 222.7 cP and more stable suspensions such that no settling was observed up to 30 minutes. The nanofiber properties were also studied and it was shown that high polymer concentrations yielded the thickest nanofibers with diameters ranging between 290.59 nm to 506.41 nm. It was further observed that FeMMT filled nanofibers have relatively larger diameters, i.e. 111.80 nm to 506.41 nm, than the ZVIMMT filled nanofibers which have diameters ranging between 84.63 nm to 445.10 nm. Bead formations were observed in some of the products wherein it is formed from suspensions with low viscosities ranging between 76.2 cP and 11.6 cP. It was, however, shown that both fibers and beads in the nanofiber have approximately the same content of montmorillonite. It was also found that the clay particles were intercalated with polymer. Further, it was revealed that FeMMT in the nanofiber have a larger interlayer spacing than the ZVIMMT particles in the nanofiber. A relationship was deduced between the suspension and nanofiber properties where finer fibers are obtained with lower viscosity and lower suspension bulk voltage. Also, bead formation was favored by lower viscosity and higher tension of the suspension.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines, Diliman.
Keywords: Polycaprolactone -- Electrospinning